2021
DOI: 10.1111/dar.13266
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relationship between cannabis use and hypertension

Abstract: Introduction The relationship between cannabis use and hypertension is not clear based on prior epidemiological studies. Thus, we examined this relationship over a 3‐year follow‐up period using a large population‐based sample from the USA. Methods Self‐reported longitudinal data were obtained from the National Epidemiologic Survey on Alcohol and Related Conditions Wave 1 (2001/2002) and Wave 2 (2004/2005). The sample was restricted to participants who did not report hypertension at baseline (n = 26 844; 51% 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Cannabis use was also related to depression development in adolescents (57). However, there was no strong evidence for the association between cannabis use, body mass index, blood lipid, and hypertension (58)(59)(60). The results of the IVW analysis were inconsistent with the results in the simple and weighted median sensitivity analyses.…”
Section: Discussionmentioning
confidence: 84%
“…Cannabis use was also related to depression development in adolescents (57). However, there was no strong evidence for the association between cannabis use, body mass index, blood lipid, and hypertension (58)(59)(60). The results of the IVW analysis were inconsistent with the results in the simple and weighted median sensitivity analyses.…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, a case report highlighted potential benefits of cannabis use on blood pressure stability in the context of autonomic dysreflexia [ 41 ]. Recently, Haleem et al found no association between cannabis use and hypertension incidence in the United States’ National Epidemiologic Survey on Alcohol and Related Conditions [ 28 ]. Elsewhere, after three months of cannabis-based treatment, blood pressure declined in 26 older adults with hypertension [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, cannabis use tends to be associated with a lower risk of meeting the criteria for metabolic syndrome diagnosis [ 24 , 25 ], which may be mediated by a body weight-lowering effect of cannabis [ 25 ]. However, contrasting results have been observed for hypertension [ 26 , 27 , 28 , 29 ] and for dyslipidemia [ 30 ] when taken individually. These various points, and the fact that cannabis use is a modifiable factor, underline the need to explore the relationships between cannabis use and metabolic disorders in HCV-infected patients in order to (i) increase understanding about the mechanisms related to extrahepatic manifestations of HCV infection, and (ii) document the metabolic impacts of cannabis use, with a view to guiding further research that may benefit both HCV-infected and non-infected people.…”
Section: Introductionmentioning
confidence: 99%
“…The available research on the effect of cannabis on blood pressure, on the other hand, appears to be contradictory. A large-population observational study showed no association of hypertension with cannabis use over a follow-up period of 12 months [ 7 ]. We evaluated the prevalence, causes, and effects of hypertensive crisis (HC) among young adults with cannabis use disorder (CUD+) to non-users in a retrospective analysis of a nationally representative cohort from the United States (US) (CUD-).…”
Section: Introductionmentioning
confidence: 99%